Malaysian Parasite Database Infrastructure - Dhillon, Sarinder; Shuhaimi, Nur-imtiazah; Lim, Lee hong; Sidhu, Amandeep (Springer-Verlag, 2013)
The Malaysian Parasite Database is set up to collect, digitize, collate, integrate and analyse available literatures on Malaysian parasites to be shared and disseminated through an integrated database system for the generation of knowledge. We adopted the data warehouse approach which is convenient and meets the purpose for the Malaysian Parasite Database. The data includes information on parasite specimens collected besides their taxonomy, biology, ecology, hosts and DNA which will be regularly updated. These data, which will be regularly updated are initially obtained from literatures and researchers collections which are then digitized and added into the database. We plan to integrate this database with other parasite host databases in order to provide a detailed and comprehensive information on indigenous parasites. This database is envisaged to be dynamic with regular incorporation of new analytical methods and novel use. In this paper, we present the infrastructure of the Malaysian Parasite Database and using a data warehouse approach which uses wrappers for a structured data extraction from related public databases and a structured vocabulary for data integration. The current and future implementations of the proposed infrastructure will be hosted on a cloud environment.